Patient and Physician Perspectives of Diabetic Retinopathy and Diabetic Macular Edema Diagnosis, Treatment and Progression: A Podcast Article - Daniel Newman; Bernadette Warren; Randall Barker; Charles C. Wykoff; Stela Vujosevic (Ophthalmology and Therapy)
Abstract Diabetic retinopathy (DR) is one of the leading causes of vision loss among people of working age. However, people with diabetes are often unaware of the importance of DR screening for preserving vision, highlighting the importance of patient education about DR and DR-related ocular and systemic comorbidities. In this podcast, three patients with different stages of DR and two ophthalmologists exchanged their views on diagnosis, treatment, and progression of DR and diabetic macular edema. The discussion revealed that DR affects not only the physical aspects of patients’ lives but also their mental wellbeing. The challenges of a DR diagnosis can be compounded by communication gaps that exist between patients, physicians, and the pharmaceutical industry. Development of new therapies is currently informed mainly by physician perspectives. However, the large burden of current treatments calls for new therapeutic approaches that meet patients’ needs better. The preferred method of treatment administration can differ from patient to patient and the choices between treatments that necessitate repeated visits, monitoring, and at-home care must be discussed. As such, going forward it is crucial to consider both the physician and patient perspectives in shaping the clinical landscape of DR.